Practicality of learning devices in problem-based learning implementation in contextual teaching and learning approach - Abdulrahman Djou; Trisnawaty Junus Buhungo; Supartin Supartin; Asri Arbie (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2022)
This study aimed to describe the practicality of physics learning tools with a problem-based learning model with a contextual teaching and learning approach. The research was conducted at Muhammadiyah Batudaa high school, and the research sample used was class XI using a simple random sampling technique. This development research uses the ADDIE model developed by Reiser and Mollenda, which consists of the analysis, design, development, implementation, and evaluation stages. The practicality test is carried out at the implementation stage. The results showed that the average percentage of the implementation of learning carried out for two meetings using a problem-based learning model with a contextual teaching and learning approach reached 97.619% with very good criteria. Then for teacher responses, 100% agreed through a teacher response questionnaire, and for student responses, 83% gave positive responses through student response questionnaires. In conclusion, physics learning tools that use a problem-based learning model with contextual teaching and learning approaches are practical to be applied in the physics learning process.